Truyện cổ tích Đông Nam Á - Trần Công Diếu (Giáo dục, 2001)
Gồm các truyện: The man who loved gold, The unfortunate hunter, The wise king, How singapore got its name, The magic jar, The king's boatman, The monkeys of mindanao,...